Determinants of Patient Preference for Private Hospitals Over Public Hospitals: An Empirical Study - Ghimire, Anisha; Barmashakha, Siwani (NPRC Journal of Multidisciplinary Research, 2024)
Introduction: There are several choices when it comes to choosing the type of hospital. In Nepal, the general public is free to seek medical attention from any facility they feel is suitable for them. People have to make vital decisions while choosing a hospital because these decisions relate to health and relieve them from any burden regarding their health. There is a preference for private hospitals over public ones. Despite the relatively cheaper cost of care in public hospitals, such a setup was not preferred by the people; this observation motivated us and created a need to conduct a research study to validate the observation statistically. This study examines reasons why private hospitals are preferred by patients over public ones. Methods: The quantitative description research methodology has been adopted for this study. Developmental research approach is used in conducting this study through quantitative descriptive research. The researcher has followed a deductive research approach to examine the hypotheses we had set up with respect to their significance. Only 117 responses out of the 120 persons of the sample were found to be significant for the research study. A structured questionnaire was designed based on a five-point Likert scale. Random sampling was selected because of the probability sampling methodology used for the research study. Findings: In Tarkeshwor Municipality, the general public does not select a private hospital over a public hospital considering their income. There is no visible relation between the level of hospital services, treatment costs, and hospital selection criteria with income level of respondents. Three dependent variables—service quality, cost, and individual selection motive—have an influence on hospital choice decisions. The vast majority of the respondents appeared to make some kind of valuation about the value for money of the hospitals they visited, irrespective of their income. Since there exists a strong positive correlation between the cost and service mean, they attach higher costs to higher quality of service. Service quality: When asked about service quality, most of the respondents replied that what inclined their preference towards private hospitals and not government-run ones was the short waiting time and up to date medical equipments. Conclusion: Hence, based on this, it can be concluded that the choice of hospitals among the public is determined in view of the cost of treatment and hospital selection motives, such as access to up-to-date medical technology and lesser wait times and so on, rather than by income, which is not related to any of the dependent variables: service quality, treatment costs, and selection motives for hospitals.